The influence of product quality brand image and price on purchasing decisions pixy lipstick products in Cikarang - Lea Afriyani; Primaraga Sumantri Indra Wicaksana (Enrichment : Journal of Management, 2023)
Purchasing decisions are several steps taken by consumers before deciding to buy a product. Purchase decisions are influenced by factors of income, price and product benefits. Therefore, business actors need to have an advantage compared to their competitors so that consumers can be interested in trying it and then make a decision to buy. The purpose of this research is to find out how product quality, brand image and price influence consumer decisions to buy Pixy lipsticks. The research method used is quantitative with a sample of 100 Pixy lipstick consumers. For data collection includes observation, distribution of questionnaires and literature study. The analytical method used is validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis testing using SPSS version 25. Based on the tests that have been carried out it is known that the three independent variables namely product quality, brand image and price are partially influential. positive and significant to the dependent variable, namely purchasing decisions. Suggestions from researchers are for companies to analyze good strategies related to selling prices, product quality, and maintaining the image of the brand they have.